The Carbon Footprint of Different Construction and Demolition Waste Management Methods (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
End-of-life management with three CDW fractions are considered in this study: wood, steel, and broken concrete. The goal of the study is to evaluate the Global Warming Potential (GWP) of different end-of-life management approaches and to benchmark the circular approaches versus the linear approaches. In the case of waste wood, the circular scenario refers to wood recycling and the production of recycled particle board or glue-laminated timber. Waste wood landfilling and the production of particle board/glue-laminated timber from primary wood are considered in the linear scenario. Considering the production of particle board, the circular scenario shows 4 times lower GWP than the linear scenario. Considering the production of glue-laminated timber, the circular scenario shows comparable GWP as the linear scenario. In the case of waste steel, the GWP of two circular scenarios were compared; recycling versus reuse. The reuse scenario shows around 8 times lower GWP than the recycling. In the case of waste concrete, the circular scenario refers to the recycling of broken concrete into recycled aggregate. The linear scenario includes the landfilling of waste concrete and the production of natural aggregate. LCA results show around 2 times lower impact on GWP in the case of the circular scenario.